Factors associated with the registration process on the initial education centers - Siu Lanzas, Julissa (2013)
This paper has the purpose of raising a reflection regarding f the conditions that lead to those responsible for the families to the incorporation of the children to the first link in the system of formal education, initial education. The possible relationship of demographic factors, family nature as well as social ones.  Consider the relevance of the study of each of these factors, enables the improvement on the management of the centers of initial education, the imminent presence of multifactorial complexity which becomes a great challenge for the administration of education. Stands out among the main conclusions that school attendance continues to represent  a basic challenge to the educational leadership, increased by the particularities of the divergence in social contexts, and the effective management of information in the planning directive, could become one of the corrective effects for trying to  neutralize the environmental variables,  among which  the formation of the family is emphasized.